If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7x + -45 = 3x Reorder the terms: -45 + 5x + 7x = 3x Combine like terms: 5x + 7x = 12x -45 + 12x = 3x Solving -45 + 12x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -45 + 12x + -3x = 3x + -3x Combine like terms: 12x + -3x = 9x -45 + 9x = 3x + -3x Combine like terms: 3x + -3x = 0 -45 + 9x = 0 Add '45' to each side of the equation. -45 + 45 + 9x = 0 + 45 Combine like terms: -45 + 45 = 0 0 + 9x = 0 + 45 9x = 0 + 45 Combine like terms: 0 + 45 = 45 9x = 45 Divide each side by '9'. x = 5 Simplifying x = 5
| 2t*3s= | | (5u+2)(8+u)=0 | | 12x-40=5x+9 | | 3x-2xy+5y= | | 5(x-14)=3x | | 4x+8=3x+16 | | 56-4x=4 | | 49^(1/2) | | 3(w-5)=6w+1-2(-6w-1) | | m*25=31.25 | | 22y+16*8=6y | | 60x/(5x)= | | y=2sin(2x+9) | | 3xy(5xy^3-3xy+5y^2)=0 | | 0.5+2.3=1.65 | | 2x+2y=39 | | x+7=5ywhatisx | | x+7=5y | | y=n+48 | | -6(x+3)-16=18+2 | | 20/0.19 | | 205=6x+3(-7x+12) | | 8=96 | | 8x-1=6x+45 | | u-3+2(3u+2)=-3(u+1) | | 5x*x^2= | | 60x(5x)= | | 3(m-5)-6=3(m+3) | | 3*2a= | | y=(x-4)2 | | 7(z-5)-6(2-3z)=12(Z+1) | | (2x-3)(3x+2)=(x-1)(x+1)+(5x+2)(x-14) |